Rainfall characteristics of Johor Bahru and Kota Bharu, Malaysia - Md Ali, Zarina; Lai, Wai Tan; Daud, Ira Masyra; Ahmad, Noor Aliza (UTHM Publisher, 2017)
Characteristics of rainfall was influenced by climate variability. Occurrence of extreme events due to climate variability may lead to flash floods or monsoonal flooding. This paper discusses on characteristics and trend of monthly and annual rainfall at Johor Bahru and Kota Bharu. Daily rainfall observations at the stations that spans over 13 years, i.e. from year 2004 to year 2016 was used. Minimum and maximum total annual rainfall recorded at Johor Bahru and Kota Bharu are 1708.0 mm and 3455.5 mm, and 1036.3 mm and 3037.0 mm, respectively. Mann-Kendall test has showed that the monthly and annual rainfall trends at both stations are insignificant. Longer period of rainfall observations should be considered to obtain more significant trends. The longest dry and wet days within a month observed over the 13-year rainfall are 26 days and 17 days at Johor Bahru, and 29 days and 25 days at Kota Bharu. Both Johor Bahru and Kota Bharu receives higher rain during the beginning of north-east monsoon, i.e. in November and December